Pengukuran Tinggi Gelombang Laut Menggunakan Sensor Ultrasonik Berbasis Internet of Things (IOT) - Deddy Bakhtiar; Anadila Ashari; Ervina Nurlaila Herliany; Lia Julianti (Jurnal Kelautan Tropis, 2024)
Disaster mitigation efforts in coastal areas require information on wave data in situ and accurately, for this reason technology is needed that can measure wave height data in realtime and continuously in order to monitor wave height easily. The purpose of this research is to develop a wave height measurement buoy device equipped with an underwater ultrasonic sensor with data transmission via the internet network. The research stages of developing an internet-based sea wave height measurement tool are designing hardware and software, collecting wave height data and testing the accuracy of the tool. The hardware is a floating buoy, IoT module consisting of JSN-SR04T ultrasonic sensor, ESP 8266 Wemos D1 microcontroller, battery, and router. This tool is connected to the ThingSpeak IoT platform as a database server so that it can be accessed in real time. The results showed that the hardware and software developed functioned well to measure data and send wave height data in real time and continuously. JSN-SR04T sensor measurement data and direct measurements have a significant relationship with a correlation coefficient of 0.56. The validation test results show that the measurement has a storage deviation or error of 8.32% due to the sensitivity of the sensor and the delay in sending data (delay) on average 2 seconds. The coefficient of determination shows that the corrected sensor data can explain 30.9% of the actual sea level data, and the remaining 69.1% is influenced by other factors.